2018
DOI: 10.20411/pai.v3i1.242
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Markers of Immune Activation Differentially Normalize and Selectively Associate with Improvement in AST, ALT, Albumin, and Transient Elastography During IFN-Free HCV Therapy

Abstract: Background:During chronic hepatitis C virus (HCV) infection, Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT) levels mark active liver inflammation and tissue damage, while albumin reflects synthetic liver function and nutritional status. Transient Elastography (TE) is a clinical measure of liver stiffness that facilitates evaluation of liver damage stage. While a portion of the TE score is attributable to liver fibrosis and relatively irreversible damage, another component of the TE score i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
28
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 39 publications
10
28
1
1
Order By: Relevance
“…In our study overall, HCV clearance after DAA therapy promoted a signi cant improvement in severity scores of liver cirrhosis and many plasma biomarkers linked to in ammation (bacterial translocation, in ammatory response, and endothelial dysfunction) and coagulopathy. Our data are in concordance with a large number of previous studies that found a signi cant decrease in liver disease scores of HIV/HCV-coinfected patients [6,7,32,[43][44][45] and HCV-monoinfected patients [6][7][8][9][10][11][12][13][14] after HCV eradiation with DAA therapy; and also in plasma biomarkers of HIV/HCV-coinfected patients [18,[30][31][32][33][34] and HCV-monoinfected patients [15][16][17][18][19][20]. However, there is an important lack of consistency in these previous publications regarding the plasma biomarkers and liver severity scores evaluated, time-points used to take data or samples after the end of HCV treatment, statistical analysis used, and liver brosis stages included.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study overall, HCV clearance after DAA therapy promoted a signi cant improvement in severity scores of liver cirrhosis and many plasma biomarkers linked to in ammation (bacterial translocation, in ammatory response, and endothelial dysfunction) and coagulopathy. Our data are in concordance with a large number of previous studies that found a signi cant decrease in liver disease scores of HIV/HCV-coinfected patients [6,7,32,[43][44][45] and HCV-monoinfected patients [6][7][8][9][10][11][12][13][14] after HCV eradiation with DAA therapy; and also in plasma biomarkers of HIV/HCV-coinfected patients [18,[30][31][32][33][34] and HCV-monoinfected patients [15][16][17][18][19][20]. However, there is an important lack of consistency in these previous publications regarding the plasma biomarkers and liver severity scores evaluated, time-points used to take data or samples after the end of HCV treatment, statistical analysis used, and liver brosis stages included.…”
Section: Discussionsupporting
confidence: 93%
“…Previously published studies do not usually have a control group of HCV-monoinfected patients, or if they do, they do not analyze the impact of HIV infection on the evolution of plasma biomarkers and liver disease scores after HCV eradication with all-oral DAAs [18,[30][31][32][33][34]. In our study, baseline values of outcome measures (plasma biomarkers and liver disease scores) and their subsequent evolution after DAA therapy were very similar in HIV/HCV-coinfected and HCV-monoinfected patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports suggested that the achievement of SVR with DAA therapy improves hepatic fibrosis in CHC patients [23,25]; however, the changes of serum ATX levels have been investigated in scarce studies in this context [16,[26][27][28] and its ability to reflect the regression of hepatic fibrosis remains uncertain. Therefore, we aimed to investigate the impact of achieving SVR with DAA therapy on serum ATX levels and whether these levels can reflect the regression of hepatic fibrosis in CHC patients.…”
Section: Introductionmentioning
confidence: 99%